2013
DOI: 10.5489/cuaj.858
|View full text |Cite
|
Sign up to set email alerts
|

Cross ectopic multicystic dysplastic kidney with ureterocele in nonectopic site

Abstract: Crossed renal ectopy (CRE) is the second most common fusion anomaly of the kidney, with an incidence of 1 in 7000 autopsies; it comes in second after horseshoe kidney. Crossed renal ectopy is associated with an ectopic ureter and generally an ectopic kidney fused with a normal kidney. A 7-month-old boy who had left-toright crossed non-fused renal ectopy and multicystic renal dysplasia with ureterocele in nonectopic kidney was reported in English language literature. In this article, we present the first case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Anal atresia was present in a boy and in another, more severe anomalies like hydrocephalus, scoliosis, meningomyelocele and pes equinovarus were seen. [5] Multicystic dysplasia was also observed in two cases similar to our case [9,12] Abdominal aortic aneurysm was reported in one case. [10] Renal ectopia occurs due to defects in the normal process of ascent of the kidney which also affects the axial rotation resulting in the anomalous position of the hilum.…”
Section: Discussionsupporting
confidence: 83%
“…Anal atresia was present in a boy and in another, more severe anomalies like hydrocephalus, scoliosis, meningomyelocele and pes equinovarus were seen. [5] Multicystic dysplasia was also observed in two cases similar to our case [9,12] Abdominal aortic aneurysm was reported in one case. [10] Renal ectopia occurs due to defects in the normal process of ascent of the kidney which also affects the axial rotation resulting in the anomalous position of the hilum.…”
Section: Discussionsupporting
confidence: 83%
“…Although the exact incidence of this anomaly is not known because majority of patients are asymptomatic, a prevalence of 1:2000 to 1:7000 has been found in autopsy series ( 7 , 8 ). Boyan et al ( 1 ) reported two male adults with left-to-right inferior crossed renal ectopia with fusion; both had a history of chronic abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…CRE has been reported in 1 : 2000 to 1 : 7000 autopsies [1]. Fusion of the ectopic kidney to the contralateral orthotopic site is present in 80–90% of cases [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Crossed renal ectopia (CRE) is a congenital anomaly where the ectopic kidney crosses the midline with the ureter at the ureterovesical junction (UVJ) remaining in a contralateral position. CRE has been reported in 1 : 2000 to 1 : 7000 autopsies [ 1 ]. Fusion of the ectopic kidney to the contralateral orthotopic site is present in 80–90% of cases [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%